Colors in dreams and the introduction of color TV in Germany: an online study - König, Nina; Heizmann, Luisa; Schredl, Michael (International journal of dream research, 2017)
Visual elements are important ingredients of dreams, so dream objects should be – based on the continuity hypothesis of dreaming – as colorful as the waking world. However, the percentages of recalled colored versus black and white dreams as estimated by the participants varied considerably across studies. In the present online study, 2701 persons completed a question about recalling colors in their dreams with three options: percentage of black and white dreams, percentage of colored dreams, and percentage of dreams with no memory of colors. The older participants who most likely had watched black and white TV reported higher recall of black and white dreams than younger persons while the younger group with access to colored TV estimated that their dreams include more often colors compared to the older group. Since the attitude towards dreams and dream recall frequency were positively associated with the reporting of colored dreams, one might hypothesize that dreamers may attribute colors to a dream even if they are do not remem ber the colors of their actual dreams. In order to validate the present findings, future studies should include the amount of media consumption (TV, cinema etc.) over the life span of the individual and elicit possible confounding factors like age-related memory changes, attention to colors in waking life, and emotional valence of colored dream elements.